1982
DOI: 10.3758/bf03330026
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of three methods of measuring recognition memory in high and low academic achievers

Abstract: This study compared three commonly used methods of measuring recognition memory (single-item, embedded•item, and multiple-choice tests) under conditions in which the targets and distractors were the same for all tests. The multiple-choice test resulted in higher recogni• tions and lower false • recognitions than the other two tests. High academic achievers had higher recognition scores than low achievers on all tests, but the interaction between achievement level and type of test showed the high achievers to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1987
1987
1988
1988

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In a recently published study of distractor-free tests of recognition , Ley and Long (1987) reported data that supported Wallace's (1980) observation that recognition memory can be measured independently of distractors (Wallace, 1978(Wallace, , 1982Wallace, Sawyer, & Robertson, 1978). Ley and Long also demonstrated that false recognitions can be measured in distractor-free tests if the test list follows a single-item presentation procedure (Ley & Karker, 1982) in which all of the targets are presented prior to presentation of distractors. This procedure revealed that the observed number of false recognitions was greater under the discrimination test than under the distractor-free test.…”
mentioning
confidence: 95%
“…In a recently published study of distractor-free tests of recognition , Ley and Long (1987) reported data that supported Wallace's (1980) observation that recognition memory can be measured independently of distractors (Wallace, 1978(Wallace, , 1982Wallace, Sawyer, & Robertson, 1978). Ley and Long also demonstrated that false recognitions can be measured in distractor-free tests if the test list follows a single-item presentation procedure (Ley & Karker, 1982) in which all of the targets are presented prior to presentation of distractors. This procedure revealed that the observed number of false recognitions was greater under the discrimination test than under the distractor-free test.…”
mentioning
confidence: 95%